Integrative review: do antihypertensive drugs have additional effects on post-exercise hypotension (PEH)? (Research, Society and Development, 2022)
Lifestyle and eating habits are factors that influence the quality of life of individuals and when these variables occur in a negative way, such as excessive use of alcohol and processed foods, they become factors that contribute to the emergence of Chronic Noncommunicable Diseases (CNCD), such as Arterial Hypertension (AH). Treatment can occur with the insertion of antihypertensive drugs (pharmacological route) and physical exercise (non-pharmacological route). However, there are gaps regarding investigations between the combination of these two therapies. The study aims to analyze through an integrative review whether the hypotensive effect of physical exercise is potentiated by the use of antihypertensive drugs. Method: integrative review, with research carried out in the journals: GOOGLE ACADÉMICO, MEDLINE, PUBMED, SCIELO AND LILACS, with the descriptors in Portuguese and English of the words: physical exercise, antihypertensive, hypotension. Results: The final sample consisted of 7 articles selected after the inclusion and exclusion criteria. Conclusion: The use of Angiotensin Receptor Blockers (ARB), IECA, Diuretics (thiazide and potassium sparing) and Calcium Channel Blockers (CCB) can potentiate the hypotensive effect of physical exercise. However, the number of studies on this topic is limited, which requires more robust experimental designs.